Emergency contraception subsidy in Canada: a comparative policy analysis - Sabrina C. Lee; Wendy V. Norman (BMC, 2022)
Abstract Background In Canada, cost prohibits access to emergency contraception (EC) which may assist to prevent unintended pregnancy. The drug, ulipristal acetate (UPA-EC), is more clinically effective and cost-effective than the prior standard levonorgestrel (LNG-EC). We analyzed provincial EC subsidization policies and examined underlying decision-making processes. Methods We undertook documentary analysis of provincial EC subsidization policies in publicly available drug formularies. We conducted semi-structured interviews with key informants to explore the processes underlying current policies. Results Quebec is the only province to subsidize UPA-EC, whilst all ten provinces subsidize LNG-EC. As such, provincial EC subsidization policies do not align with the latest UPA-EC evidence. Interviews revealed that evidence was valued in the policymaking process and formulary decisions were made through interdisciplinary consensus. Conclusions We identify a gap between EC subsidization policies and the latest evidence. Institutional structures affect policies reflecting evolving evidence. Increasing interdisciplinary mechanisms may encourage evidence-based policies.